Low latitude ionosphere-thermosphere dynamics studies with inosonde chain in Southeast Asia - T. Maruyama (2018)
An ionosonde network consisting of a meridional chain and an equatorial pair was established in the Southeast Asian area. Three of four ionosondes are along the magnetic meridian of 100° E; two are close to the magnetic conjugate points in Northern Thailand and West Sumatra, Indonesia, and the other is near the magnetic equator in the Malay Peninsula, Thailand. The fourth ionosonde is also near the magnetic equator in Vietnam but separated by about 6.3° towards east from the meridional chain. For a preliminary data analysis, nighttime ionospheric height variations at the three stations of the meridional chain were examined. The results demonstrate that the coordination of the network has a great potential for studying ionosphere/thermosphere dynamics. Through the assistance of model calculations, thermospheric neutral winds were inferred and compared with the HWM93 empirical thermospheric wind model. Higher-order wind variations that are not represented in the empirical model were found.